Self-perception and participation in sports and exercise : a comparison of obese and normal weight adolescents in a secondary school - Low, Christina Peck Khay. (2008)
The main purpose of this study was to investigate if the self-perception as well as sports and exercise participation of obese adolescents were significantly different from that of normal weight adolescents in a secondary school. The study compared the obese and normal weight adolescents with regard to their perceived competence in six domains of their lives. The domains comprised (1) scholastic competence (2) social competence (3) athletic competence (4) physical appearance (5) behavioral conduct and (6) close friendship. For these two groups of adolescents, the variable, global self-worth was compared. In addition, the study explored gender differences in the self-perception profile and sports and exercise participation of adolescents.